Modeling the Short-Run Consumption Function in Iraq: The Role of Income and Government Expenditure (1981–2021) - Bahram Mahmood Salih (AL-ARBAH: Journal of Islamic Finance and Banking, 2026)
Purpose - This study examines the drivers of short-run household consumption in Iraq, testing whether income or government expenditure dominates demand dynamics in a rentier economy. Method - Using annual data (1981–2021), we employ Structural Vector Autoregression (SVAR) with impulse response functions and forecast error variance decomposition alongside OLS regressions. Variables include household consumption, GDP, and government expenditure, all I (1) integrated with one cointegrating relationship. Result - Fiscal shocks produce immediate and sustained consumption increases, while GDP effects are weak or negative (coefficient: –0.46, p<0.05 versus +0.98, p<0.01 for government expenditure). Variance decomposition reveals government spending explains 17% of consumption volatility in year one, rising to 55% by year ten. GDP shocks remain minor throughout all horizons. Implication - Iraq's consumption dynamics reflect fiscal dominance rather than conventional income-driven patterns. Policymakers should prioritize stable, household-targeted expenditure and establish fiscal buffers against oil price volatility to stabilize household welfare across economic cycles.. Originality - This is the first long-horizon SVAR analysis of Iraq's consumption function, challenging Keynesian income-centric models and providing structural evidence of fiscal transmission channels in resource-dependent, post-conflict economies where state redistribution substitutes for private income generation. Keywords: consumption function, fiscal policy, government expenditure, structural VAR, Iraq, rentier economy